A influência da marca na decisão de compra de produtos religiosos - Sousa, João Henrique Viana de (2011)
The western society has become increasingly oriented to consumption, from the second half of the 20th century, because of the social, economic, political and technological changes that occurred at high speed. In this context, understanding consumer behavior has become a vital necessity not only for companies but for the entire market-oriented organization. In nowadays, there is the influence of the brand, linked to the consumer's purchase decision. This paper aims to understand the linkages between: the market of religious products, the influence of the brand, consumer behavior and purchasing decisions. The overall goal of this dissertation is to investigate the influence of the brand in purchase decision of consumers of religious products.